The MOSAIC study - comparison of the Maudsley Model of Treatment for Adults with Anorexia Nervosa (MANTRA) with Specialist Supportive Clinical Management (SSCM) in outpatients with anorexia nervosa or eating disorder not otherwise specified, anorexia nervosa type: study protocol for a randomized controlled trial. - Schmidt, U; Renwick, B; Lose, A; Kenyon, M; Dejong, H; Broadbent, H; Loomes, R; Watson, C; Ghelani, S; Serpell, L; Richards, L; Johnson-Sabine, E; et al. (2013)
BACKGROUND: Anorexia nervosa (AN) is a biologically based serious mental disorder with high levels of mortality and disability, physical and psychological morbidity and impaired quality of life. AN is one of the leading causes of disease burden in terms of years of life lost through death or disability in young women. Psychotherapeutic interventions are the treatment of choice for AN, but the results of psychotherapy depend critically on the stage of the illness. The treatment response in adults with a chronic form of the illness is poor and drop-out from treatment is high. Despite the seriousness of the disorder the evidence-base for psychological treatment of adults with AN is extremely limited and there is no leading treatment. There is therefore an urgent need to develop more effective treatments for adults with AN. The aim of the Maudsley Outpatient Study of Treatments for Anorexia Nervosa and Related Conditions (MOSAIC) is to evaluate the efficacy and cost effectiveness of two outpatient treatments for adults with AN, Specialist Supportive Clinical Management (SSCM) and the Maudsley Model of Treatment for Adults with Anorexia Nervosa (MANTRA). METHODS/DESIGN: 138 patients meeting the inclusion criteria are randomly assigned to one of the two treatment groups (MANTRA or SSCM). All participants receive 20 once-weekly individual therapy sessions (with 10 extra weekly sessions for those who are severely ill) and four follow-up sessions with monthly spacing thereafter. There is also optional access to a dietician and extra sessions involving a family member or a close other. Body weight, eating disorder- related symptoms, neurocognitive and psychosocial measures, and service use data are measured during the course of treatment and across a one year follow up period. The primary outcome measure is body mass index (BMI) taken at twelve months after randomization. DISCUSSION: This multi-center study provides a large sample size, broad inclusion criteria and a follow-up period. However, the study has to contend with difficulties directly related to running a large multi-center randomized controlled trial and the psychopathology of AN. These issues are discussed.